In vitro characterization of TMPRSS2 inhibition in IPEC-J2 cells. (2nd November 2016) - Pászti-Gere, Erzsebet; Czimmermann, Eszter; Ujhelyi, Gabriella; Balla, Peter; Maiwald, Alexander; Steinmetzer, Torsten
Abstract: The transmembrane serine protease, TMPRSS2 is an important target in the treatment of seasonal influenza infections and contributes to prostate carcinogenesis and metastasis. In this study, the effect of the synthetic TMPRSS2 inhibitor I-432 on jejunal IPEC-J2 cell monolayers cultured on membrane inserts was characterized. Using a fluorogenic substrate, it was found that the apical addition of I-432 could suppress trypsin-like activity in the supernatants of IPEC-J2 cells. The inhibition of TMPRSS2 did not affect physiologically produced hydrogen peroxide levels in the apical and in basolateral compartments. Loss of expression of the TMPRSS2 serine protease domain (28 kDa) was also observed when cells were pre-exposed to I-432. Partial decrease in immunofluorescent signal intensities derived from the altered distribution pattern of TMPRSS2 was detected after a 48 h long incubation of IPEC-J2 cells with the inhibitor indicating the efficacy of TMPRSS2 inhibition via I-432 administration in vitro .